Adages Ii1 to Iv100 - Erasmus, Desiderius, -1536 (Erasmus, Desiderius, -1536. Works. 1974, 1982)
Erasmus' Adagia has been called 'one of the world's biggest bedside books,' and certainly the more than 4000 proverbs and maxims gathered and commented on by Erasmus, sometimes in a few lines and sometimes in full-scale essays, have great appeal for both scholar and educated layman. The aim of the Adages was to recapture, in this handy portmanteau form, the outlook and way of life of the classical world through its customs, legends, and social institutions, and to put within reach of a modern public the accumulated wisdom of the past. Each adage is traced in the works of as many authors as Erasmus had to hand; always an authority is given (usually several) and often a close reference providing chapter and verse.The commentaries in the Adages give a forthright and often eloquent expression of Erasmus' opinions on the world of his day, dovetailing with his satirical works on the one hand and his popular evangelical writings on the other. Many, if not most, of the proverbs cited by Erasmus are still in our common stock of speech today.The Collected Works of Erasmus is providing the first complete translation of Erasmus' Adagia. This volume contains the initial 300 adages with notes that identify the classical sources and indicate how Erasmus' reading and thinking developed over the quarter-century spanned by the eight revisions of the original work.